أثر نظم المعلومات التسويقيَّة على فاعلية القرارات التسويقيَّة للمنشآت الزراعية في الساحل السوري. - جحجاح, محسن; عليو, محمود; زرقة, أبو العلاء (Latakia University Journal -Biological Sciences Series, 2017)
يهدف البحث إلى معرفة أثر نظم المعلومات التسويقيَّة على فاعلية القرارات التسويقيَّة للمنشآت الزراعيَّة، اعتُمد المنهج المسحي التحليلي الذي يعتمد على دراسة الظاهرة كما توجد في الواقع، وإجراء المسوحات الميدانية للحصول على البيانات من مصادرها الرئيسة من خلال الاعتماد على أداة البحث، وهي الاستبيان.أظهرت نتائج البحث من خلال تحليل البيانات التي تمَّ جمعها من أفراد عينة البحث بواسطة الاستبيان النتائج:1. أنَّ مُستوى الاهتمام باستخدام بحوث التسويق في جمع المعلومات التي تهم مُنشآتهم، وإجراء دراسات للأسواق، والزبائن، وأي مُتطلبات لتطوير خدماتهم أو أي معلومات ضروريَّة في المُنشآت الزراعيَّة المبحوثة كان مرتفعاً.2. يوجد أثر ذو دلالة إحصائيَّة لنُظم المعلومات التسويقيَّة (السجلات الداخليَّة، بحوث التسويق) مُجتمعة على فاعلية القرارات التسويقيَّة في المُنشآت الزراعيَّة، وقد بلغت قوة معامل الارتباط (0.773) ومُعامل التحديد (0.598) مما يعكس ارتفاع قوة هذه العلاقة ودرجة تفسير مُتغيرات نُظم المعلومات التسويقيَّة لمُتغير فاعلية القرارات التسويقيَّة.3. يوجد أثر ذو دلالة إحصائية لاهتمام بالسجلات الداخليَّة في المُنشآت الزراعيَّة على فاعلية القرارات التسويقيَّة، وقد بلغت قوة معامل الارتباط (0.64) ومُعامل التحديد (0.409) مما يعكس ارتفاع قوة هذه العلاقة ودرجة تفسير مُتغير الاهتمام بالسجلات الداخليَّة لمُتغير فاعليِّة القرارات التسويقيَّة.The research aims to find out the impact of marketing information systems on the effectiveness of marketing decisions for agricultural facilities, screening analytical method which is based on the study of the phenomenon adopted and there are, in fact, conduct field surveys to obtain data from sources key by relying on the search tool, a questionnaire.And it proved through the data collected from the research sample by questionnaire analysis following results:1. Research proved that the level of interest in using marketing research to gather information of interest to their facilities, and studies of markets, customers, and any requirements for the development of their services or any necessary information in the agricultural firms surveyed was high.2 . There is the impact of a statistically significant for marketing information systems (internal records, marketing research) combined on the effectiveness of marketing decisions in agricultural facilities, it has reached the correlation coefficient strength (0.773) and the coefficient of determination (0.598), reflecting the rising strength of this relationship and the degree of interpretation of marketing information systems variables the variable effectiveness of marketing decisions.3. There is a statistically significant effect of the interest of the internal records in agricultural facilities on the effectiveness of marketing decisions, it has reached the correlation coefficient strength (0.64) and the coefficient of determination (0.409), reflecting the rising strength of this relationship and the degree of interpretation of variable interest in the internal records of the variable effectiveness of marketing decisions.